Hubungan Aktivitas Fisik dengan Kejadian Dismenore Pada Remaja Putri di SMPN 3 Simpang Raya - Reza F.A.A; Deswinda Deswinda; Puswati D; Adelia G (Universitas Malahayati, 2026)
ABSTRACT Dysmenorrhea is a prevalent reproductive health condition among adolescent girls and may disrupt daily functioning, including school-related academic activities. physical activity is considered one of the factors associated with the occurrence of dysmenorrhe. Insufficient physical activity may affect blood circulation and hormonal balance, thereby increasing the risk of menstrual pain. The objective of this study was to assess the relationship between physical activity and dysmenorrhea among female adolescents at SMP Negeri 3 Simpang Raya.The investigation applied quantitative techniques via a cross-sectional study design. All adolescent girls at SMP Negeri 3 Simpang Raya constituted the study population, and the entire population of 107 respondents was included using total sampling. Data collection was conducted using a physical activity questionnaire and a menstrual pain scale. The data analysis involved univariate analysis to depict respondent characteristics and bivariate analysis to examine the association between physical activity and dysmenorrhea. Participant demographics showed that respondents clustered around early adolescence, with a mean age of 13.64 ± 0.97 years, while the mean age at menarche was 11.63 ± 1.06 years. Most respondents experienced dysmenorrhea with mild to moderate pain intensity. The majority of respondents had low levels of physical activity. Bivariate analysis indicated a significant relationship between physical activity and the incidence of dysmenorrhea among adolescent girls. In conclusion, there is a significant relationship between physical activity and dysmenorrhea among adolescent girls at SMP Negeri 3 Simpang Raya. Regular physical activity can help reduce menstrual pain intensity by improving blood circulation and stimulating endorphin release. Therefore, it is recommended that adolescent girls engage in regular physical activity as a non-pharmacological strategy to prevent and reduce dysmenorrhea. Keywords: Physical Activity, Adolescent Girls, Dysmenorrhea. ABSTRAK Dismenore adalah suatu permasalahan masalah kesehatan reproduksi yang kerap dialami remaja putri dan mengganggu rutinitas harian, termasuk aktivitas belajar di sekolah. Faktor yang diduga memiliki keterkaitan dengan kejadian dismenore salah satunya yaitu aktivitas fisik. Aktivitas fisik yang kurang dapat memengaruhi sirkulasi darah dan keseimbangan hormonal sehingga meningkatkan risiko nyeri menstruasi. Penelitian ini dimaksudkan guna mengkaji hubungan antara aktivitas fisik dan kejadian dismenore pada remaja putri di SMP Negeri 3 Simpang Raya. Pendekatan kuantitatif dengan desain cross-sectional dipergunakan dalam penelitian ini, di mana seluruh remaja putri di SMP Negeri 3 Simpang Raya menjadi populasi penelitian, dengan total sampel 107 responden mempergunakan teknik total sampling. Data diambil mempergunakan kuesioner aktivitas fisik dan skala nyeri menstruasi. Data dianalisis secara univariat guna menggambarkan karakteristik responden, serta secara bivariat agar diketahui keberadaan hubungan antara aktivitas fisik dan dismenore. Diperlihatkan dengan temuan ini bahwasanya responden rata-rata berusia 13,64 ± 0,97 tahun dan usia menarche rata-rata adalah 11,63 ± 1,06 tahun. Banyaknya responden mengalami dismenore ringan hingga sedang. Mayoritas responden memperlihatkan rendahnya tingkat aktivitas fisik. Analisis bivariat mengindikasikan adanya hubungan signifikan antara aktivitas fisik dengan kejadian dismenore pada remaja putri. Kesimpulan yang didapatkan adalah terdapat hubungan antara aktivitas fisik dengan kejadian dismenore pada remaja putri di SMP Negeri 3 Simpang Raya. Rutinitas dalam beraktivitas fisik dapat membantu menurunkan keluhan nyeri haid karena mampu melancarkan sirkulasi darah serta merangsang pelepasan hormon endorfin. Oleh sebab itu, remaja putri dianjurkan untuk membiasakan diri melakukan aktivitas fisik secara teratur sebagai cara nonfarmakologis dalam upaya pencegahan dan pengurangan keluhan dismenore. Kata Kunci: Aktivitas Fisik, Remaja Putri, Dismenore.